(untitled) (BIRDEM Medical Journal, 2019)
Background: Approximately one third of all colorectal cancers are rectal cancers. It is a peculiar malignancy as resection of this cancer may lead to loss of anal sphincter and the patient is condemned to a permanent colostomy. Aim of the surgery is oncological clearance and sphincter preservation. The optimal surgical management of rectal cancer requires detailed preoperative planning and to determine a logical approach to the management of this complex disease by analyzing the factors that determine its surgical outcome. This study was done to obtain a clear understanding of the factors determining the oncological clearance and sphincter preservation in low rectal carcinoma and thereby guiding surgeons to take appropriate decision in the surgical management. Methods: This prospective observational study, involving 60 consecutive patients with low rectal cancer, was done in Sir Salimullah Medical College and Mitford Hospital, from January 2013 to December 2015. Data were prospectively collected, using detailed proforma and analyzed with a Statistical Package for the Social Sciences (SPSS) version 18.0 and the results were presented in tables. Results: Out of the 60 patients, 40 (67%) had oncological clearance and 26 (43%) had sphincter preservation. A statistically significant number of patients with T1-T2 tumor had oncological clearance [40 (83%) vs 8 (17%), p<0.05]. None of the patients with T3-T4 tumor had curative resection. Whereas, a statistically significant number of patients with tumor distance beyond 5 cm from anal verge, had sphincter preservation [32 (94%) vs 2 (6%), p<0.05]. Most of the patients with tumor within 5 cm [24 (94%) out of 26] had sphincter resection. Conclusion: Tumor factors, favoring sphincter preservation, were ³5 cm distance from anal verge, whereas, circumferential spread limited to muscularis propria (T1-T2), favored oncological clearance. Birdem Med J 2020; 10(1): 16-20